Becoming a law to regulate the production and use of chemicals: the problems of technical regulation - Бабенко, О. С. (Problems of legality, 2013)
The system of legal regulation of the management of chemicals in Ukraine, although it has become a development, but is very imperfect. The main problems concerning technical legislation, the resolution of which will improve the systems of standardization and certification focused on European practice.